First-principles study of structural, electronic and thermoelectric properties of nidoped Bi2 Se3 - Muhammad Zamir Mohyedin,; Mohamad Fariz Mohamad Taib,; Afiq Radzwan,; Masnawi Mustaffa,; Amiruddin Shaari,; Ul-Haq, Bakhtiar; Oskar Hasdinor Hassan,; Muhd Zu Azhan Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Direct conversion of waste heat to electrical energy could address present energy challenges. Bi2 Se3 is one of few thermoelectric materials known to operate at room temperature. Comprehensive analysis using density functional theory was conducted to explore the effect of nickel doping on structural, electronic, and thermoelectric properties of Bi2 Se3 . Local density approximation (LDA) was used with an addition of spin-orbit coupling (SOC) and van der Waals interaction scheme consideration. Analysis of the effect of SOC was elaborated. It was found that nickel has changed the crystal structure of Bi2 Se3 . Nickel has also changed band structure and density of state that alter the thermoelectric performance. The decreased band gap has decreased the thermopower. However, it gives advantages to the improvement of electrical conductivity. Higher electrical conductivity has risen thermal conductivity. Despite the decreased thermopower and increased thermal conductivity, the higher electrical conductivity has improved the overall thermoelectric performance of Bi2 Se3 when nickel is introduced.